Fé e informação: uma análise do processo de produção do telejornal Canção Nova Notícias - Sá, Regiane de Andrade (2024)
When narrating an event, the news is framed in a perspective of reality influenced by several factors, such as news values, the editorial line and the experiences of journalists. This work aims to discuss the production process of news broadcast by the news program Canção Nova Notícias, from the Catholic broadcaster TV Canção Nova. Taking as a basis theoretical assumptions from the theory of Newsmaking (WOLF, 1999; VIZEU, 2014; TUCHMAN, 2016; PENA 2018), Religion (FRAZER, 1922; RATZINGER, 1970; ELIADE, 1992; DURKHEIM, 1996; BERKENDROCK, 2019; BLANC , 2021) of Communication and Religion (MARQUES DE MELO, 1985; MARTÍN-BARBERO, 1995; FAUSTO NETO, 2001; GOMES, 2004; PUNTEL, 2011; SBARDELOTTO, 2012; MIKLOS, 2013; MARTINO, 2017; GASPARETTO, 2019; RENGA , 2021), and Telejournalism (PATERNOSTRO, 1987; BARBEIRO E LIMA, 2002; VIZEU, 2009; BELÉM, 2017) seeks to analyze the news routine, through investigation of the influence of the institution's religious values and professional culture of journalists. The main question of this research is to understand to what extent religious factors influence newsworthiness criteria and how news selection and production mechanisms are applied. The methodological path of this study consisted of 6 stages: bibliographical review, document analysis, analysis of television audiovisual content, participant observation, interview and interpretation of the results achieved, which confirmed the hypothesis that the religious values of Catholic-inspired broadcasters influence routines production processes and professional practices in the news construction process and in the forms of organization of this vehicle. Even so, even though they are permeated with Christian principles, the commitment to journalistic production seems to take into account broad contexts such as public interest and reality, constructing factual narratives defined as being more positive and light.